La colonisation valaque sur les versants nord des Carpates pendant le Petit Âge Glaciaire (aux XVe et XVIe siècles) - Jawor, Grzegorz (Balcanica Posnaniensia. Acta et studia, 2019)
The Wallachian settlement on the northern slopes of the Carpathians in the Little Ice Age (15th and 16th century). A significant deterioration of the climate took place in the Carpathians in the period from the 15th to the 19th century. It was a fragment of a global phenomenon referred to by various representatives of geoscience as the Little Ice Age (LIA). Arguments presented in the article were preceded by a preliminary assumption that these events had a particular impact on the living conditions of populations who inhabited the areas situated in the sub-mountain and mountain zones in the 15th and 16th century. Located in this area were the upper levels of various cultivated plants’ ranges, which were particularly crucial for the cultivation of winter cereal crops. Even minor fluctuations of multi-annual average temperatures could significantly increase or decrease them. The results contained in this work were formed on the basis of information from the sources, which are primarily of a fiscal nature and which so far have been underrated by historians of the climate. The analysis of changes taking place in individual settlements was conducted on the other hand by using the methodology applied by historians of human settlement. The outcome of the studies presented below offers a general conclusion on the existence of a widespread phenomenon in the discussed period of an increase in the Carpathian areas of elements from a model of the economic functioning of the village life which was based on stockbreeding. This happened at the expense of restricting or sometimes even eliminating agricultural activities. It was the main reason for which individual landowners fostered or initiated colonization based on the Wallachian law or, at least, on its elements. For this reason, the 16th century in particular became a period of a sudden development of this settlement trend in the Carpathian regions. This had serious consequences not only for the economy. The study draws attention to the fact that the introduction of these changes could take place due to the migration of ethnically foreign people who were acquainted with the secrets of a specialised stockbreeding, which was unavailable to classical farmers. Amongst the newcomers were also ethnic Vlachs. One of the consequences of these migrations was also a considerable increase in the scope of the Orthodoxy at the expense of Catholicism in Lesser Poland.